Research on the Preparation of Self-nano-emulsifying Drug Delivery System Containing Gynostemma pentaphyllum Dry Extract for Application in Skin Care Cosmetics - Giang, Vu Thi Thu; Thuy Hanh, Pham; Van Lam, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 39 No 1DO - 10.25073/2588-1132/vnumps.4488, 2023)
Abstract: Gynostemma pentaphyllum (Thunb.) Makino is a rich source of the herb in Vietnam. The gypenosides in this herb are triterpenoid saponins that have been shown to have moisturizing, antioxidant, and anti-aging effects on the skin. However, gypenosides are hydrophilic and have a large molecular weight with a bulk molecular structure which prevents them from penetrating and absorbing into the skin. To apply the natural active ingredients from herbs into skin care cosmetics, this research developed self-nano-emulsifying drug delivery systems (SNEDDS) containing Gynostemma pentaphyllum dry extract and applied them to emulgel skin care cosmetics. Prepared SNEDDS could self-emulsify in the water to form nanoemulsions with dispersed droplet sizes less than 20 nm with PDI < 0.3. The proportion of saponin entrapped in the oil droplets of nano emulsification was more than 90%. When combined with emulgel excipients, the obtained cosmetic products had nano-sized dispersed droplets less than 200 nm with uniform droplet size distribution, which are promising for application when further research is carried out. Keywords: Self-nano-emulsifying Drug Delivery System (SNEDDS), Gymnostemma pentaphyllum dry extract, cosmetic, emulgel, nano-emulsion.